Lipid nanoparticles enhance the efficacy of mRNA and protein subunit vaccines by inducing robust T follicular helper cell and humoral responses - Alameh, Mohamad-Gabriel; Tombácz, István; Bettini, Emily; Lederer, Katlyn; Ndeupen, Sonia; Sittplangkoon, Chutamath; Wilmore, Joel R.; Gaudette, Brian T.; Soliman, Ousamah Y.; Pine, Matthew; Hicks, Philip; Manzoni, Tomaz B.; et al. (Immunity (Cambridge, Mass.), 2021)
Adjuvants are critical for improving the quality and magnitude of adaptive immune responses to vaccination. Lipid nanoparticle (LNP)-encapsulated nucleoside-modified mRNA vaccines have shown great efficacy against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but the mechanism of action of this vaccine platform is not well-characterized. Using influenza virus and SARS-CoV-2 mRNA and protein subunit vaccines, we demonstrated that our LNP formulation has intrinsic adjuvant activity that promotes induction of strong T follicular helper cell, germinal center B cell, long-lived plasma cell, and memory B cell responses that are associated with durable and protective antibodies in mice. Comparative experiments demonstrated that this LNP formulation outperformed a widely used MF59-like adjuvant, AddaVax. The adjuvant activity of the LNP relies on the ionizable lipid component and on IL-6 cytokine induction but not on MyD88- or MAVS-dependent sensing of LNPs. Our study identified LNPs as a versatile adjuvant that enhances the efficacy of traditional and next-generation vaccine platforms. [Display omitted] •LNPs are immunostimulatory and act as an adjuvant component of modified mRNA vaccines•LNP-adjuvanted protein subunit vaccines foster potent Tfh cell and humoral responses•LNPs are not sensed by receptors signaling through MyD88 or MAVS•IL-6 induction and the ionizable lipid are critical for the adjuvant activity of LNPs The mechanism of action of nucleoside-modified mRNA-LNP vaccines is unknown. Alameh et al. demonstrate that LNPs can possess adjuvant activity and promote robust induction of Tfh cell, B cell, and humoral responses when utilized in mRNA and protein subunit vaccines in mice. IL-6 induction and the ionizable lipid component are critical for the adjuvant activity of LNPs.